ANALISIS KEPUASAN USER DALAM LAYANAN SISTEM INFORMASI AKADEMIK TERPADU (SIMPADU) PADA POLITEKNIK NEGERI BANJARMASIN MENGGUNAKAN PIECES FRAMEWORK - Irawan, Agus; Mantala, Ronny; Risa, Mey (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
SIMPADU was born to answer the need for information within the Banjarmasin State Polytechnic academic community as a form of information service. This research aims to provide recommendations/ suggestions/input in the form of policies to improve the quality of the Integrated Academic Information System (SIMPADU) in the Banjarmasin State Polytechnic academic environment. SIMPADU is a website-based application created to assist the data management process of academics, lecturers and students in 5 departments (21 study programs) and is useful in managing campus management at the Banjarmasin State Polytechnic. Policy suggestions prepared based on an analysis process for assessing the Banjarmasin State Polytechnic information system with a comparison of the dimensions of the PIECES Framework to measure the quality of SIMPADU as a guide in improving or developing service quality. The analysis results are processed using the PIECES Framework method based on assessment criteria (Very Good/Good/Fair/Poor). It is hoped that the results of the recommendations in this research can contribute to Poliban management, especially the Academic Section, through UPT ICT as a reference material or decision support in improving the quality of the website-based Integrated Academic Information System (SIMPADU) to be even better in the future.